2019
DOI: 10.1002/slct.201900048
|View full text |Cite
|
Sign up to set email alerts
|

Development of One‐Step Water‐Repellent and Flame‐Retardant Finishes for Cotton

Abstract: Pyrovatex is a well-known commercial flame-retardant which is commonly applied for cotton fibers. Unfortunately, Pyrovatex has the concern of discharging toxic formaldehyde, and additionally it necessitates formaldehyde-based cross-linking agents to enhance the flame retardant character and durability. Thus, formaldehyde level is considerably increased in the treated cotton fabrics. Herein, we develop a simple approach toward superhydrophobic and flame-retardant coating for cotton fabrics. We apply one-bath pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 53 publications
(53 reference statements)
0
39
0
Order By: Relevance
“…However, cotton fabrics are extremely flammable, threatening human life and property . The flame retardant cotton fabric can delay the spread of flame; furthermore, it can improve the flame‐retardant, self‐extinguishing and smoke‐eliminating properties of cotton fabrics …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, cotton fabrics are extremely flammable, threatening human life and property . The flame retardant cotton fabric can delay the spread of flame; furthermore, it can improve the flame‐retardant, self‐extinguishing and smoke‐eliminating properties of cotton fabrics …”
Section: Introductionmentioning
confidence: 99%
“…[5] The flame retardant cotton fabric can delay the spread of flame; furthermore, it can improve the flame-retardant, self-extinguishing and smoke-eliminating properties of cotton fabrics. [6][7][8] Phosphorous compounds are considered to be the most promising efficient flame retardants for cotton fabrics. [9,10] Phosphorous-containing compounds generate phosphoric acid at high temperature, then condense to pyrophosphoric acid after dewatering, next, pyrophosphoric acid further forms polymetaphosphate, and the cellulose structure of the cotton is carbonized to obtain an expanded char layer in this process, thereby preventing combustion and obtaining dense char residue.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the heavy metallic soaps possess superhydrophobic characteristics, and consequently the primary effort at the manufacture of a durable water-repellent finishing was to employ the chromium salt of a fatty acid to be applied on cotton followed by baking. The most recent water-repellent finishing processes include the application of fluorocarbons which are essentially an ester of perfluorinated hexanol with polyacrylic acid [ 67 , 68 ].…”
Section: Functional Finishing Of Technical Textilesmentioning
confidence: 99%
“…Technical textiles are high-performance smart materials designed not just to appear good-looking, but also to introduce a considerable added functional value toward a better quality of life [1][2][3]. Technical textiles have been applied in modern society for various specialized applications, such as antimicrobial, super hydrophobic, anti-static, ultraviolet protection, flame-retardant and self-cleaning purposes [4][5][6][7][8]. Nanotechnology can be considered as one of the most significant emerging global technologies.…”
Section: Introductionmentioning
confidence: 99%